Fossil bog soils ('dwog horizons') and their relation to Holocene coastal changes in the Jade Weser region, southern North Sea, Germany - Scheder, Juliane; Engel, Max; Bungenstock, Friederike; Pint, Anna; Siegmüller, Annette; Schwank, Stephan; Brückner, Helmut (Journal of coastal conservation, 2018)
After the deceleration of the postglacial marine transgression, the German North Sea coast was subject to deposition of a complex pattern of subtidal to terrestrial facies. This study aims at reconstructing these facies changes in the 'Land Wursten' region (Lower Saxony) by focussing on socalled dwog horizons (incipient soil horizons of the pre-engineered salt marshes). We explore their implications for relative sea-level reconstructions and their indication for early settlement activities. Archive drilling data (1960, provided by the 'Landesamt für Bergbau, Energie und Geologie') were analysed to create five high-resolution stratigraphie cross sections. Three new drilling records were subjected to sedimentological and microfaunal investigations and interpreted to verify and calibrate the archive data. Two dwog horizons were found and ¹⁴C-AMS dated. We found basal salt marsh deposits inundated by a high-energy event and covered by tidal flat sediments. The thick tidal flat unit is again overlain by salt marsh deposits indicating the transition from a shallow marine to a terrestrial environment where dwogs were developed and covered by episodic marine incursions. The ages of the dwogs (1128-969 cal BC cal AD 1426-1467) do not correlate with known layers of adjacent settlement sites and are critically discussed. However, we show that they correlate with phases of stagnant regional relative sea level (RSL) and can be used as RSL indicators. The combined archive and modern data provide valuable information for the RSL reconstruction and palaeoenvironmental changes. However, further research is recommended to accomplish more detailed information about coastal response during the Holocene sea-level changes and implications for settlement dynamics.